Implementasi ERP Odoo untuk Peningkatan Sistem Informasi Bisnis Perusahaan menggunakan Metode Accelereted SAP - Anjani, Diyan; Hikmawan, Rizki; Sari , Dian Permata (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
The development of information technology in the business world is important for companies, one of which is the development of information systems in solving problems and managing various business transactions. Implementing ERP in companies is one of the developments in business information systems. This research aims to implement the Odoo ERP system business processes to improve the company's business information system so that work can be more efficient and integrated in one business process. The Odoo application was implemented using the Accelerated SAP method starting from the project preparation phase to the final preparation phase. Analysis was carried out by observation and interviews. This research involved 1 Acount Recevaibel staff member, and 1 HRD at PT Tiara Fajar Transportindo as research subjects. System testing using black box is carried out to minimize errors in the functions used.. The findings show that the document module, recruitment module and employee module in the Odoo application can be used as an update to the existing business system. Testing in black box tasting shows that the system is in accordance with expectations. Therefore, implementing the Odoo application is suitable for use at PT Tiara Fajar Transportindo.